Prevalence and Subtypes Distribution (ST10, ST14, ST25, ST26) of Blastocystis spp. in Anatolian Water Buffalo (Bubalus bubalis) in Van, Türkiye - Adnan Ayan; Burcak Aslan Celik; Ozgur Yasar Celik; Ali Bilgin Yilmaz; Ozlem Orunc Kilinc; Ozge Oktay Ayan (Veterinary Medicine and Science)
ABSTRACT Background Blastocystis spp. is one of the most common protozoa worldwide, living in the gastrointestinal tract of humans and many other animals. On the basis of the genetic heterogeneity of small subunit ribosomal RNA, at least 28 subtypes (ST1‐ST17, ST21 and ST23–ST32) are reported to exist in mammals and birds. Objectives This study was carried out to determine the prevalence and subtypes of Blastocystis spp. in Anatolian buffaloes (Bubalus bubalis) in Van province in the Eastern Anatolia Region of Turkey. Methods DNA was extracted using commercial GeneMATRIX Stool DNA Purification Kit and then stored at −20°C until PCR amplification. After PCR amplification of the SSU rRNA gene region positive Blastocystis spp., amplicons from buffalo faeces were sequenced and then deposited in GenBank (OR576949.1, OR576950.1, OR576970.1, OR576971.1, OR577019.1, PP837943.1, PP837940.1, PP837939.1, PP837604.1, PP837937.1, PP837934.1, PP837601.1, PP837936.1 and PP837603.1). Results PCR analysis of 120 faecal samples showed a total prevalence of 11.67% (14/120). The prevalence was higher in females and young animals (p > 0.05). Sequence analysis revealed Blastocystis spp., ST10, ST14, ST25 and ST26 subtypes. To our knowledge, Blastocystis subtypes ST25 and ST26 in buffaloes were reported for the first time in this study. Conclusion It is thought that more large‐scale studies should be carried out to determine the zoonotic subtype potential of this protozoan in the region.